Oceans'10 Ieee Sydney 2010
DOI: 10.1109/oceanssyd.2010.5603866
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of exhaust emissions of marine traffic using Automatic Identification System data (case study: Madura Strait area, Indonesia)

Abstract: The Madura Strait area is one of the busiest marine traffic regions in Indonesia. Many ships arrive, depart and travel through that area, thus influencing the air quality of the port environment. Furthermore, the Indonesian government has not yet ratified Marine Pollution (MARPOL) 73/78 Annex VI regarding the prevention of air pollution from ships and the absence of restricting regulations could have an influence on the level of air pollution. In this study, an Automatic Identification System (AIS) receiver is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Emissions are calculated by considering factors such as engine and fuel type of each type of fuel. Pitana et al (2010) has shown that emission rate can be calculated using Equation 3 as below.…”
Section: Fc Bhpxsfocxtmentioning
confidence: 99%
See 1 more Smart Citation
“…Emissions are calculated by considering factors such as engine and fuel type of each type of fuel. Pitana et al (2010) has shown that emission rate can be calculated using Equation 3 as below.…”
Section: Fc Bhpxsfocxtmentioning
confidence: 99%
“…Where: E = The total emission of pollutants (kg) S = The fuel consumption (ton/hours) F = The emission factor (kg/ton of fuel) Pitana et al (2010) has shownthe emission factor of each pollutant in units of kg per ton fuel and the type of ship engines in Table 2.…”
Section: Estimation Of Ship Exhaust Gasmentioning
confidence: 99%
“…There are many utilizing AIS data for conducting researches, for instance, the usage of AIS data for estimation marine exhaust emission, development of hazard navigation map, ship evacuation assessment and dangerous score [6] [7][8][9] [10]. It seems that the previous researches have not been combined as the system for monitoring the marine safety and environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers propose methods for estimating CO 2 and PM emissions from ships using Automatic Identification System (AIS) data in Baltic Sea [4] or in Madura Strait area [5], but there is no papers related to the strait of Gibraltar. Furthermore, these methods do not take into account real-time emissions.…”
Section: Introductionmentioning
confidence: 99%